2012
DOI: 10.1016/j.bmc.2012.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, biochemical studies, cellular characterization, and structure-based computational studies of small molecules targeting the urokinase receptor

Abstract: The urokinase receptor (uPAR) serves as a docking site to the serine protease urokinase-type plasminogen activator (uPA) to promote extracellular matrix (ECM) degradation and tumor invasion and metastasis. Previously, we had reported a small molecule inhibitor of the uPAR•uPA interaction that emerged from structure-based virtual screening. Here, we measure the affinity of a large number of derivatives from commercial sources. Synthesis of additional compounds was carried out to probe the role of various groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
47
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 57 publications
2
47
0
Order By: Relevance
“…However, recent experimental evidence indicates that some members of the MMP family behave as tumor-suppressor enzymes and may therefore be regarded as antitargets in cancer therapy (46). Moreover, small-molecule inhibitors of uPA binding to uPAR have been recently described (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent experimental evidence indicates that some members of the MMP family behave as tumor-suppressor enzymes and may therefore be regarded as antitargets in cancer therapy (46). Moreover, small-molecule inhibitors of uPA binding to uPAR have been recently described (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…This effect was further enhanced by addition of the exogenous uPA due to the release of fully activated Lb and was partially abolished by the addition of PAI-1. Because it was confirmed that the NSCLC cells produce uPA, 24 this may partially contribute to the inhibitory effect of KPLK on cell proliferation. In contrast, the normal cell line (HSGC) with the same treatment was unaffected, suggesting that both KPLK and Lb were not toxic to normal cells.…”
Section: Discussionmentioning
confidence: 97%
“…6,7) Therefore, inhibition of the expression and activity of ECM degradation enzymes is important in arresting cancer cell invasion and metastasis. [8][9][10] Since transcription factor nuclear factor kappa B (NF-κB) is a major mediator of inflammation, as well as a regulator of cancer cell development and progression. Many reports have been demonstrated that NF-κB signaling has a critical role in cancer cells metastasis.…”
mentioning
confidence: 99%